2016
DOI: 10.21511/ppm.14(2).2016.06
|View full text |Cite
|
Sign up to set email alerts
|

Female directorship, director compensation, managerial shareholding, and price-earnings multiple of Nigerian firms

Abstract: The failure of business entities across the globe has continued to draw the attention of stakeholders of those entities. Due to these problems, different countries issued corporate governance regulations to avoid the repeat of the past. Part of the aims of these CG guides is to increase firm value. In Nigeria, similar guidelines issued for firms are referred to as codes of CG. However, arguments exist between stakeholders on whether those corporate governance mechanisms increase the value of shareholders. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Also, it has been observed that the quantitative factors (ROA, CAR, and NPA) are better in private sector banks than in public and NBFCs, where ROA and CAR show a positive relation with P/BV, and NPA is negatively related to P/BV. 85 Fairfield and Patricia, 42 Block 23 2. Accounting variables Return on asset ROA It is a profitability ratio that shows the percentage of profit generated by the assets.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been observed that the quantitative factors (ROA, CAR, and NPA) are better in private sector banks than in public and NBFCs, where ROA and CAR show a positive relation with P/BV, and NPA is negatively related to P/BV. 85 Fairfield and Patricia, 42 Block 23 2. Accounting variables Return on asset ROA It is a profitability ratio that shows the percentage of profit generated by the assets.…”
Section: Discussionmentioning
confidence: 99%
“…Price Book Value berganda dapat menurun atau meningkat melalui semua ekuitas, menghasilkan pengembalian saham yang lebih rendah atau lebih tinggi. Oleh karena itu, harga untuk nilai buku berganda memainkan peran penting dalam memperkirakan pengembalian saham perusahaan (Shittu, Ahmad, & Ishak, 2016). Nilai pasar adalah nilai saham dipasar, yang ditunjukkan oleh harga saham tersebut dipasar (Eduardus Tandelilin, 2010).…”
Section: Pendahuluanunclassified